2020
DOI: 10.1002/aenm.202000931
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Encapsulation of Sulfur in a MOF‐Derived S, N‐Doped Porous Carbon Host Realized via the Vapor‐Infiltration Method Results in Enhanced Sodium–Sulfur Battery Performance

Abstract: Practical applications of room temperature sodium–sulfur batteries are still inhibited by the poor conductivity and slow reaction kinetics of sulfur, and dissolution of intermediate polysulfides in the commonly used electrolytes. To address these issues, starting from a novel 3D Zn‐based metal–organic framework with 2,5‐thiophenedicarboxylic acid and 1,4‐bis(pyrid‐4‐yl) benzene as ligands, a S, N‐doped porous carbon host with 3D tubular holes for sulfur storage is fabricated. In contrast to the commonly used m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
94
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(95 citation statements)
references
References 49 publications
(59 reference statements)
1
94
0
Order By: Relevance
“…MOF-derived carbon is very effective as a sulfur host for MS batteries. 57 Conventional porous carbon materials that are used as sulfur host MOFs bind to sulfur passively. Thus, the grip of carbon materials on sulfur is not very good, leading to less sulfur loading and also the dissolution of sulfur.…”
Section: Ms Batteriesmentioning
confidence: 99%
“…MOF-derived carbon is very effective as a sulfur host for MS batteries. 57 Conventional porous carbon materials that are used as sulfur host MOFs bind to sulfur passively. Thus, the grip of carbon materials on sulfur is not very good, leading to less sulfur loading and also the dissolution of sulfur.…”
Section: Ms Batteriesmentioning
confidence: 99%
“…[66] Porous Carbon Material-Based Sulfur Hosts: Porous carbon architectures with large specific surface areas and abundant pores are promising hosts for Na-S batteries. [67][68][69][70][71][72] The large specific surface area and high pore volume not only ensure a high sulfur content in the composite cathodes but also alleviate the volume changes of sulfur. In addition, the high electrical Figure 3.…”
Section: Carbon/sulfur and Other Sulfur Composite Cathodesmentioning
confidence: 99%
“…Rogach et al reported a MOF-derived S, N co-doped porous carbon skeleton with 3D tubular holes for Na-S batteries (Figure 5a). [72] Using a vapor-infiltration method, sulfur species were bonded with the carbon structures; this method is different from the commonly employed melt-diffusion method to physically confine sulfur species. The sulfur cathodes demonstrated outstanding electrochemical performance with high capacities (467 mAh g −1 at 0.1 A g −1 , 270 mAh g −1 after 1000 cycles at 1.0 A g −1 ) and excellent rate capability (304 mAh g −1 at 10 A g −1 ).…”
Section: Carbon/sulfur and Other Sulfur Composite Cathodesmentioning
confidence: 99%
See 1 more Smart Citation
“…For another, Li 2 S is prone to accumulating at the cathode side, which is not easy to be efficiently dissociated.Recent years have witnessed a burgeoning interest in designing adsorptive and electrocatalytic mediators for effective PS management in Li-S realm, in order to essentially expedite redox kinetics and inhibit "shuttle effect." [14][15][16][17][18][19][20] Although strenuous efforts have been devoted to exploring various types of PS mediators including carbonaceous materials, [21][22][23][24][25] metal oxides/carbides/nitrides/borides/ sulfides/selenides/phosphides, [26][27][28][29][30][31][32][33][34][35][36] and heterostructures, [37][38][39][40][41][42][43][44] their unsatisfactory adsorptive and catalytic behavior caused by insufficient active sites remains a huge barrier for obtaining favorable Li-S chemistry. To circumvent this problem, adjusting the morphology of PS mediators such as reducing their size to nanoscale has been recognized as a promising method to expose more active lattice planes and edge sites.…”
mentioning
confidence: 99%